Fiktion im Vergleich der Künste und Medien - Enderwitz, Anne, 1974-; Rajewsky, Irina O., 1968- (WeltLiteraturen., 2016)
""Fiction research has traditionally developed its theories from narrative texts. While narratology has engaged in media comparisons for some time, such comparisons are still at an early stage in fiction theory. This volume examines the phenomena of fiction through a comparative arts and media perspective, thereby helping to create a theory of fiction grounded in transmediality."--